Explorative Study of Hadith as a Source of Islamic Law about Falak - Zulfiyah Zulfiyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
Islam is very complex in various fields of science. One of the sciences that must be learned is Falak. This study discusses hadith as a source of Islamic law in relation to the sign of celestial knowledge. This research is a library research by exploring the texts of the hadith of the Prophet Muhammad related to astronomy information. The results showed that astronomy is very closely related to the command of Allah Almighty. related to human worship includes the Qibla direction, prayer times, Islamic calendar, eclipse of the moon and sun. Based on this, the study of astronomy is a fardhu kifayah for Muslims to help the perfection of the worship of Allah Almighty.